“Okay sir, I’m gonna ask you to sign here”: Closing sequences as collaborative social action in traffic encounters - Shon, Phillip Chong Ho 19XX- (Criminology & criminal justice, 2024)
The police are more likely to arrest, write citations, and reciprocate with coercive responses that involve warnings and threats when citizens disrespect and resist the police. Warnings in natural discourse are considered to be benevolent and differ from threats only in the intention and attitude of those who issue such speech acts. This article examines how ordinary features of talk-in-interaction are adapted to meet the institutional exigencies of patrol work, and how the interactional order of closing sequences in traffic encounters are collaboratively produced by police and drivers alike. We analyze 50 traffic encounters involving mundane infractions such as speeding and running a red light from the United States using principles of conversation analysis. Our findings indicate that closing sequences can be viewed as mutually accomplished social action in three distinct ways that are similar to and different from ordinary conversations. The implications for police studies and procedural justice research are discussed.